VERBAL IRONY AND FLOUTING MAXIMS IN BAD TEACHER MOVIE - NASTITI, LARASATI DWIKI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key Terms: Verbal Irony, Maxim, Flouting of Maxim, Implicature, Bad Teacher Movie. Movie is one of entertainment media which can reflect daily life, especially in terms of the conversation. This study discusses flouting maxims through verbal irony occur in Bad Teacher Movie. The problem of this study is what kinds of flouting maxim occur through verbal ironies uttered by the characters in Bad Teacher Movie and what are the implied meanings.This study used qualitative approach since the data were in the form of the transcript of Bad Teacher Movie. The writer collected the data by reading the transcript and found verbal ironies which flout the maxims. After that, the writer identified the kinds of maxim being flouted, analyzed them, and drew conclusion. In analysing the implied meanings of the ironical utterances, the writer consider the context occurs in the movie and interpret the implied meanings based on the context.The writer found that all of maxims are flouted by the characters through 21 verbal ironies. The most frequently flouted maxim is maxim of quality which is found in 21 utterances. The second are maxim of relation and maxim of manner which are found in 4 utterances for each maxim. The least is maxim of quantity which is found in 3 utterances. Also, there are 9 verbal ironies which flout more than one maxim. The flouting maxims occur mostly because the characters give false contribution in a conversation.The writer suggests that the next researchers relate some aspects of verbal irony or flouting maxims with other theories for example politeness theory. The next researchers are also suggested to conduct similar study in another different object such as novel, talk show, or radio show.